Hubungan Shift Kerja Dengan Kelelahan Kerja Pada Perawat UGD Dan Ruang Bangsal RSUD Piru Kabupaten Seram Bagian Barat - Ira Sandi Tunny (Pusat Riset dan Inovasi Nasional, 2021)
The Relationship between Work Shift and Work Fatigue in the Emergency Room Nurses and the Ward Room of RSUD Piru, West Seram Regency in 2020. Therefore, shift work every day, namely the morning shift starting at 08.00-17.00 WIT while the night shift starts at 17.00-08.00 WIT. The health of nurses is very important so that health services in the community can be optimal, considering that nurses are human resources who play an important role in the hospital for 24 hours. And one of the efforts to improve the quality of service with work shift regulations. Work shifts need to be considered the time or biological clock that corresponds to our body for work accidents. Work fatigue contributes to the occurrence of work accidents caused by fatigue factors. This type of research uses quantitative research with a cross-sectional study design (cross-sectional) where measurement of the variables can be done at the same time so that it is quite effective and efficient. Research subjects were taken 30 nurses from the ER and Ward at PIRU Hospital. The measurement results show the relationship between work shifts and work fatigue of nurses in the ER and Ward there are 8 respondents (26.7%) who have a morning shift schedule and experience fatigue and 7 respondents (23.3%) respondents who have a night shift schedule and do not experience fatigue. The statistical test results show a significant value α <0.003, which means that Ha is accepted by Ho is rejected.